Osteoid osteoma of mandibular bone: Case report and review of the literature. Issue 5 (September 2019) - Maehara, Takashi; Murakami, Yuka; Kawano, Shintaro; Mikami, Yurie; Kiyoshima, Tamotsu; Chikui, Toru; Kakizoe, Noriko; Munemura, Ryusuke; Nakamura, Seiji
Abstract: Osteoid osteoma is a benign bone-forming tumor and characterized by its limited growth potential, not exceeding 2 cm. The radiological hallmark of this tumor is a nidus, which is a small round area of relative radiolucency. Osteoid osteoma can involve any bone but is most commonly found in long bones and is extremely rare in the head and neck region. This disease characteristically presents with dull pain, worse at night, and sometimes relieved with NSAIDs. A 24-year-old Japanese woman presented with spontaneous pain and tenderness on the lingual side of her mandibular second molar on the right side. The patient reported that her pain had gradually increased, becoming more continuous and severe and no longer responding to NSAIDs. An initial panoramic radiograph revealed an oval, internally non-uniform, somewhat obscure boundaries in the right mandible. Computed tomography (CT) scan revealed a sclerotic lesion with a delineated central calcified nidus surrounded by a radiolucent band. The interior of the nidus was a non-uniform, irregularly shaped area of high absorption. The nidus was removed with intralesional curettage under general anesthesia. The histopathology of the specimen consisted of actively proliferating osteoblasts mixed with an interlacing network of immature bone and osteoid trabeculae. Immunohistochemistry revealed that hardly detected osteoblasts or fibrous stromal cells with intense nuclear immunoreactivity for p16 and/or murine double minute 2 (mdm2). We thus distinguished the tumor from Low-grade central osteosarcoma (LGCO) with immunohistochemical findings. The histopathological diagnosis was thus osteoid osteoma.